2019
DOI: 10.4274/tjps.galenos.2018.82160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surfactant on Azithromycin Dihydrate Loaded Stearic Acid Solid Lipid Nanoparticles

Abstract: ÖZAmaç: Azitromisin dihidrat, çeşitli bakteriyel enfeksiyon tiplerinin tedavisinde kullanılan bir makrolid antibiyotiktir. Etkin madde düşük çözünürlüğü nedeniyle düşük oral biyoyararlanım gösterir. Bu çalışmada, etken maddenin çözünürlüğünü ve çözünme hızını arttırmaya yönelik olarak azitromisin dihidratın katı lipit nanopartikülleri formüle edilmiştir. Gereç ve Yöntemler: Azitromisin dihidrat yüklü stearik asit nanopartikülleri, etken madde miktarını sabit tutarken, farklı lipit yüzey aktif madde oranında üç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…So finasteride-loaded stearic acid SLNs are having more capacity of drug loading which makes them safer for use. Similar types of results were also discussed in the previous study where the SLNs of stearic acid showed drug entrapment of 68.38% [ 41 ].…”
Section: Resultssupporting
confidence: 88%
“…So finasteride-loaded stearic acid SLNs are having more capacity of drug loading which makes them safer for use. Similar types of results were also discussed in the previous study where the SLNs of stearic acid showed drug entrapment of 68.38% [ 41 ].…”
Section: Resultssupporting
confidence: 88%
“…After an appropriate dilution, absorbance was determined by UV -Spectrophotometer ((Model Shimadzu 1800, Japan)) at 288 using HSPC solution as blank, and the drug content was calculated using a calibration curve. 18 The drug loading was calculated using equation (3).…”
Section: Determination Of Drug Content and Drug Loading In Spcmentioning
confidence: 99%
“…The amounts of PVA, polysorbate 80, and PEG-400 are based on previous studies where surfactant and cosurfactant form emulsion. The amount of stearic acid was also based on a previous study with the best formula using 1 g. The planned variation point was the amount of stearic acid from 1 to 2 g (Bhattacharyya and Reddy, 2019;Mardiyanto et al, 2021;Rupenagunta et al, 2011;Sarathchandiran, 2012). The composition of the ingredients for the formulation of lipid nanoparticles can be seen in Table 1.…”
Section: Lipid Nanoparticle Formulationmentioning
confidence: 99%